P-69 Hospice enabled dementia care. the first steps. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Cooper, Marie; Richardson, Heather; Crowther, Jacqueline
Abstract : Aim of this project: To promote hospice enabled dementia care, hospices need to position themselves as key partners working with their local community and care economy to ensure people affected by dementia have access to optimum palliative and end of life care and support where ever they live and whenever they need it. This is achieved through an evidence based approach to identifying current gaps, concerns and opportunities for partnership/collaboration/research STEP 1: Recognising the need to extend hospice care to people with dementia in the future STEP 2: Bringing together a group of experts in dementia care and palliative care to consider options for the way forward STEP 3: Understanding the current level of dementia care by hospices and their concerns about extending this further STEP 4: Creating a practical guide for hospices that addresses concerns and highlights opportunities for this development. Includes a checklist to enable hospice leaders to assess the organisational readiness for success STEP 5: Open a one year funding programme for hospices who are interested to expand their care, with a view to replication across the sector if successful. Key outcomes: A series of recommendations around improved access and care for people affected by a diagnosis of dementia including: A corporate commitment to reaching out to people with dementia A collaborative approach to the development of services and skills A creative approach to the adaption of existing models of care An evidence based approach to improvement of care and the environment Investment in the development and support of the hospice workforce